2016
DOI: 10.1038/srep28387
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of microRNA-related variants associated with risk of Alzheimer’s disease

Abstract: MicroRNAs (miRNAs) serve as key post-transcriptional regulators of gene expression. Genetic variation in miRNAs and miRNA-binding sites may affect miRNA function and contribute to disease risk. Here, we investigated the extent to which variants within miRNA-related sequences could constitute a part of the functional variants involved in developing Alzheimer’s disease (AD), using the largest available genome-wide association study of AD. First, among 237 variants in miRNAs, we found rs2291418 in the miR-1229 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 60 publications
(94 reference statements)
1
48
0
Order By: Relevance
“…Genetic variants in miRNAs or miRNA-binding sites could affect miRNA function and contribute to disease risk[32, 33]. Polymorphisms within the SNCA 3’UTR have been reported, and specifically associated with PD [3438].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in miRNAs or miRNA-binding sites could affect miRNA function and contribute to disease risk[32, 33]. Polymorphisms within the SNCA 3’UTR have been reported, and specifically associated with PD [3438].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified multiple disease-associated variants within miRNA gene regions and within miRNA binding sites in target mRNAs [11,59]. Differential binding of miRNA and RBPs to 3′UTR variants have also been modeled in silico [9,10].…”
Section: Regulatory Variantsmentioning
confidence: 99%
“…For example, the G>C substitution (SNP rs138166791) in the penultimate position of pre-miR-890, significantly lowers the cleavage efficiency by DROSHA and, consequently, decreases the levels of mature miR-890-5p and miR-890-3p (46). There is also evidence that some SNPs within miRNA genes may correlate with different diseases, including cancer (47)(48)(49)(50)(51)(52)(53). Finally, there are a few examples of Mendelian diseases caused by germline mutations in miRNA genes (54)(55)(56)(57).…”
Section: Introductionmentioning
confidence: 99%